Marginal Matters : Explorations into Commenting and Glossing Techniques in Arabic Manuscript Cultures - Brinkmann, Stefani, (Bibliotheca Arabica ;, 2025)
For centuries, scribes and users have left notes in the margins of manuscripts, paraphrasing, explaining, criticising, and supplementing the main text. This volume sheds light on such scribal practices in Arabic manuscripts, investigating diverse techniques and approaches across the vast geographical and temporal range of the Arabic manuscript age. What similarities and differences can we observe regarding place, time, and subject? And what can we learn from these annotations in the margins or between the lines? This volume is the first to focus specifically on the rich tradition of marginal commentaries in Arabic manuscripts and seeks to establish the study of commentary and glossing practices as an important source for the history of Arabic literature, Islamic intellectual history, and comparative manuscript studies. Contributors are Berat Açıl, Philip Bockholt, Stefanie Brinkmann, Nadja Danilenko, Verena Klemm, Boris Liebrenz, Nadine Löhr, Darya Ogorodnikova, Deborah Schlein and Florian Sobieroj.